2016
DOI: 10.1515/ohs-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and antifouling activities of extracellular polymeric substances isolated from the bacteria associated with marine gastropod Turbo sp

Abstract: The extracellular polymeric substances (EPS) produced by the bacteria associated with the gastropod

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…For example, the inhibitory activity of polysaccharide produced by a bacterial species was previously reported by Valle et al (2006). Similarly, biofilm inhibitory activities of EPS produced by surfaceassociated marine bacteria have been demonstrated by Rajasree et al (2012Rajasree et al ( , 2014 and Viju et al (2016). Following adhesion, bacteria produce extracellular polymeric substances which are essential for cellto-cell adhesion (Azedero and Oliveira 2000) cell aggregation (Burdman et al 2000) and biofilm formation (Decho 2000).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, the inhibitory activity of polysaccharide produced by a bacterial species was previously reported by Valle et al (2006). Similarly, biofilm inhibitory activities of EPS produced by surfaceassociated marine bacteria have been demonstrated by Rajasree et al (2012Rajasree et al ( , 2014 and Viju et al (2016). Following adhesion, bacteria produce extracellular polymeric substances which are essential for cellto-cell adhesion (Azedero and Oliveira 2000) cell aggregation (Burdman et al 2000) and biofilm formation (Decho 2000).…”
Section: Discussionmentioning
confidence: 76%
“…collected from Colachel coast (West coast of India) were brought to the laboratory in a sterile plastic container with seawater. The bacteria associated with the gastropod were isolated according to the method described by Viju et al (2016). In brief, the loosely attached organisms on the surface of gastropod were removed by washing with sterile seawater.…”
Section: Collection and Isolation Of Surface Associated Bacteriamentioning
confidence: 99%
“…Marine EPS have far more complex and diverse bioactivities than terrestrial EPS [201,205]. According to the previous research, EPS exhibit many properties that can be used in wound management, including antibacterial [212][213][214], antioxidant [215][216][217], anti-inflammatory [218,219], gelforming [220], etc. In addition, several studies have reported that some marine microbial EPS could regulate wound cell metabolism to promote tissue regeneration and wound healing [215,221,222].…”
Section: Marine Microorganisms Exopolysaccharidesmentioning
confidence: 99%
“…The experiment was carried out in replicate (n=3) and the mean ± standard deviation values were considered. The percentage of bacterial growth/inhibition was calculated using the following formula (Viju et al 2016).…”
Section: Bacterial Growth Inhibition Assay (Spectrophotometer Assay)mentioning
confidence: 99%